CONSUMERS’ PREFERENCE AND WILLINGNESS TO PAY FOR RED PALM OIL AS ALTERNATIVE COOKING OIL: CHOICE-BASED CONJOINT ANALYSIS - Fatihaturrizqi, Aini Al; Pratama, Bayu Rizky; Santoso, Syahlaa' Salsabila Putri; Fitrianita, Syifa; Supriatna, Aulia Rahman; Alfath, Muhammad (Agricore, 2025)
AbstractIndonesia’s heavy reliance on palm cooking oil has significant implications for national food security. The 2022 palm oil shortage exposed vulnerabilities in supply chains, triggering sharp price volatility, panic buying, and reduced access for low-income households. In response, Red Palm Oil (RPO) emerges as a potential alternative, offering enhanced nutritional value through β-carotene and vitamin E. However, market acceptance of RPO remains limited, primarily due to low consumer awareness and resistance to its distinct red color compared to conventional cooking oil. This study aims to analyze consumers’ willingness to pay (WTP) for RPO and to evaluate the effectiveness of differentiated marketing strategies, including health-claim labeling and integrated nutritional and processing information, in improving consumer acceptance. A choice-based conjoint analysis was employed, and preferences were estimated using a conditional logit model based on data from 200 household respondents in Brebes, Central Java. The experimental design utilized fractional factorial and orthogonal arrays to construct choice sets. The results reveal that intrinsic attributes, such as red color and strong taste, negatively influence consumer preferences. In contrast, extrinsic attributes, particularly the combination of nutritional and processing information labels along with health claims, significantly enhance consumer acceptance (β= 0.513) and increase willingness to pay (WTP = Rp 18,876). These findings highlight the importance of effective labeling strategies and consumer education in promoting RPO adoption. Strengthening information delivery through integrated labeling can serve as a key policy and marketing instrument to support food diversification and improve nutritional outcomes in Indonesia.CONSUMERS’ PREFERENCE AND WILLINGNESS TO PAY FOR RED PALM OIL AS ALTERNATIVE COOKING OIL: CHOICE-BASED CONJOINT ANALYSIS